Public Hearings as Institute of Civil Society: Problems of the Organization and Realization - Larisa Dmitrievna Kozyreva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article examines the dual nature of public hearings as the civil society Institute and the Institute of deliberative democracy. Shows the essential features of public hearings as a form of civic participation, their difference from other forms of direct democracy. Main problems of organizing and conducting hearings; the proposed measures to improve their efficiency.